2002
DOI: 10.1099/00221287-148-4-909
|View full text |Cite
|
Sign up to set email alerts
|

LuxS: its role in central metabolism and the in vitro synthesis of 4-hydroxy-5-methyl-3(2H)-furanone

Abstract: Many bacteria produce extracellular molecules which function in cell-to-cell communication. One of these molecules, autoinducer 2 (AI-2), was first described as an extracellular signal produced by Vibrio harveyi to control luciferase expression. Subsequently, a number of bacteria have been shown to possess AI-2 activity in their culture supernatants, and bear the luxS gene product, which is required for AI-2 synthesis. In Porphyromonas gingivalis, luxS and pfs, encoding a 5'-methylthioadenosine/S-adenosylhomoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
336
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(364 citation statements)
references
References 55 publications
14
336
2
3
Order By: Relevance
“…Since LsrR contains a predicted HTH DNA-binding domain, it has been suggested to repress the transcription of the lsr operon and itself by directly binding to their promoters. In order to determine whether LsrR can bind to the lsrA and lsrR promoter regions, we carried out gel evidence showed that in V. harveyi, AI-2 is (2S, 4S)-2-methyl-2,3,3,4-tetrahydroxytetrahydrofuran-borate (S-THMF-borate); and in E. coli and S. typhimurium, AI-2 is (2R, 4S)-2-methyl-2,3,3,4-tetrahydroxytetrahydrofuran (R-THMF) [10,[16][17][18][19][20][21][22].…”
Section: Lsrr Binds To Lsra and Lsrr Promotersmentioning
confidence: 99%
See 1 more Smart Citation
“…Since LsrR contains a predicted HTH DNA-binding domain, it has been suggested to repress the transcription of the lsr operon and itself by directly binding to their promoters. In order to determine whether LsrR can bind to the lsrA and lsrR promoter regions, we carried out gel evidence showed that in V. harveyi, AI-2 is (2S, 4S)-2-methyl-2,3,3,4-tetrahydroxytetrahydrofuran-borate (S-THMF-borate); and in E. coli and S. typhimurium, AI-2 is (2R, 4S)-2-methyl-2,3,3,4-tetrahydroxytetrahydrofuran (R-THMF) [10,[16][17][18][19][20][21][22].…”
Section: Lsrr Binds To Lsra and Lsrr Promotersmentioning
confidence: 99%
“…In every case, AI-2 is synthesized by LuxS, which functions in the pathway for metabolism of S-adenosylmethionine (SAM), a major cellular methyl donor. In a metabolic pathway known as the activated methyl cycle, SAM is metabolized to Sadenosylhomocysteine, which is subsequently converted to adenine, homocysteine, and 4,5-dihydroxy-2,3-pentanedione (DPD, the precursor of AI-2) by the sequential action of the enzymes Pfs and LuxS [10,16]. DPD is a highly reactive product that can rearrange and undergo additional reactions, suggesting that distinct but related molecules derived from DPD may be the signals that different bacterial species recognize as AI-2.…”
Section: Introductionmentioning
confidence: 99%
“…Other bacteria, B. burgdorferi included, further degrade SRH to DPD and homocysteine via the LuxS enzyme (Babb et al, 2005;Stevenson & Babb, 2002;Stevenson et al, 2003;Sun et al, 2004;Xavier & Bassler, 2003). The majority of bacteria salvage homocysteine for regeneration of methionine, for use in additional transmethylation reactions or protein synthesis (Winzer et al, 2002). B. burgdorferi is among the minority of bacteria which lack methionine synthase, and are therefore unable to utilize the homocysteine produced by LuxS (Babb et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…1), which provides activated methyl groups for the methylation of DNA, RNA, proteins and other substrates (5,9,12,13). The LuxS/Pfs pathway, which is present in Gamma-, Beta-, and Epsilonproteobacteria as well as in Firmicutes (5), is responsible for the recycling of the toxic intermediate S-adenosylhomocysteine (SAH) to homocysteine.…”
mentioning
confidence: 99%